Pengaruh Percobaan Sains Anak Usia Dini terhadap Perkembangan Kognitif Anak di TK Kartika Siwi Pusdikpal Kota Cimahi - Yanti Mustika; Lia Nurwidaningsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The purpose of this research is to know the influence of early childhood science experiments on child cognitive development in Kartika Siwi Pusdikpal Kindergarten Cimahi. Learning early childhood science experiments at Kartika Siwi Kindergarten can help early childhood knowledge and understanding of science concepts, and help put aspects related to science skills to improve children's cognition. The research problem is whether early childhood science experiments have an effect on the cognitive development of children in Kartika Siwi Kindergarten. The research method used is experimental research method. The population of this research is all children in Kartika Siwi Kindergarten which amounted to 26 children. Sampling research using total sampling technique. Data collection using pretest and postest, documentation, as well as observation and data processing using t-test statistical formula. Based on the results of hypothesis testing that t arithmetic t table, is 8.20 2.05 so the hypothesis in this study accepted. The results showed that early childhood science experiments can affect children's cognitive development of 4.50 (good category). It is suggested to teachers to be able to improve cognitive abilities of children by using variations and innovative methods in different games so that the cognitive abilities of children can be further improved.